2002
DOI: 10.3354/meps238153
|View full text |Cite
|
Sign up to set email alerts
|

Diel vertical migration and the haemocyanin of krill Meganyctiphanes norvegica

Abstract: Changes in environmental factors (PO 2 , temperature, salinity and food availability) influence the concentration of the respiratory pigment haemocyanin ([Hc]) present in many crustaceans. We investigated the possibility that [Hc] and HcO 2 affinity altered during the diel vertical migration (DVM) of Nordic krill Meganyctiphanes norvegica in the Gullmarsfjord, Sweden. The [Hc] decreased with increasing depth, for individuals both trawled and caged at different depths. Laboratory experiments indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(70 reference statements)
1
19
0
Order By: Relevance
“…He found that at 5 C, M. norvegica haemolymph had a very low affinity for oxygen (P 50 or half saturation value ¼ 50.1 mmHg [6.66 kPa], at pH ¼ 7.9). This was very similar to P 50 values of 6.12-6.31 kPa, pH ¼ 7.80, T ¼ 7 C, recorded by Spicer and Strömberg (2002) for dialysed haemolymph from individuals collected from the Gullmarsfjord, Sweden. Brix et al (1989) also found that the cooperativity (the 'sigmoidness' of the O 2 binding curve) was high, but not exceptional (n 50 ¼ 2.5-3.0) although the haemolymph did exhibit a marked Bohr effect Physiology and Metabolism of Northern Krill (Dlog PO 2 /Dlog pH ¼ À1.99), amongst one of the highest recorded for crustaceans.…”
Section: Respiratory Pigmentssupporting
confidence: 86%
See 4 more Smart Citations
“…He found that at 5 C, M. norvegica haemolymph had a very low affinity for oxygen (P 50 or half saturation value ¼ 50.1 mmHg [6.66 kPa], at pH ¼ 7.9). This was very similar to P 50 values of 6.12-6.31 kPa, pH ¼ 7.80, T ¼ 7 C, recorded by Spicer and Strömberg (2002) for dialysed haemolymph from individuals collected from the Gullmarsfjord, Sweden. Brix et al (1989) also found that the cooperativity (the 'sigmoidness' of the O 2 binding curve) was high, but not exceptional (n 50 ¼ 2.5-3.0) although the haemolymph did exhibit a marked Bohr effect Physiology and Metabolism of Northern Krill (Dlog PO 2 /Dlog pH ¼ À1.99), amongst one of the highest recorded for crustaceans.…”
Section: Respiratory Pigmentssupporting
confidence: 86%
“…To our knowledge, M. norvegica, and krill generally, utilises just the one extracellular respiratory pigment, the copper-based haemocyanin (Hc), that is found in some crustaceans and some molluscs (Brix et al, 1989;Spicer and Strömberg, 2002). Brix et al (1989) was the first to characterise the O 2 binding properties of M. norvegica haemocyanin (Fig.…”
Section: Respiratory Pigmentsmentioning
confidence: 99%
See 3 more Smart Citations